Analisis Cakupan Jaringan 4G LTE Operator Telkomsel, XL Axiata, dan Indosat Ooredoo di Kecamatan Bayung Lencir, Kabupaten Musi Banyuasin, Provinsi Sumatera Selatan - Ariyudi (Institute of Information Technology and Social Science (IITSS), 2021)
The development of the fourth-generation (4G) cellular telecommunications network with Long Term Evolution (LTE) technology has become the backbone of data services in Indonesia. Network quality and coverage are important factors in determining user satisfaction. This study aims to analyze the 4G LTE network coverage of Telkomsel, XL Axiata, and Indosat Ooredoo in Bayung Lencir District, Musi Banyuasin Regency, South Sumatra Province. The parameters analyzed include Reference Signal Received Power (RSRP) and Signal-to-Interference-plus-Noise Ratio (SINR). Measurements were conducted in nine villages/sub-districts using the Android-based G-NetTrack Pro application. The measurement data were statistically analyzed using one-way Analysis of Variance (ANOVA). The results showed that the RSRP values of the three operators were not significantly different, indicating relatively equal received signal strength. However, the SINR parameter showed a significant difference, with Telkomsel having the highest SINR value, followed by Indosat Ooredoo and XL Axiata. These findings are expected to serve as a reference for the public in selecting cellular operators and as a basis for evaluation for telecommunications service providers.